2019
DOI: 10.35940/ijrte.c4796.098319
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Analytics: An Indian Perspective

Abstract: To gain competitive advantage and to improve efficiency, reliance on data has grown manifold. This work explored the emerging sources of big data generation in India, particularly post implementation of ‘Digital India’ scheme. Agencies that have implemented the big data are accentuated along with the potential area. Further, a model is proposed to integrate key services utilized within a country with the ‘Aadhar’ to gain insight in real time. Seamless integration of key services with ‘Aadhar’ will be increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…The system presented a graph-based crime research framework that focuses on establishing relationships between the entities found in a sizable corpus of crime data from Indian states and union territories [15]. To deal with criminal situations, big data-based data analytical approaches can be applied [16]. Additionally, many data collection techniques are used for better performance, including Web 2.0, Geographic Information System (GIS), and Volunteered Geographic Information (VGI).…”
Section: Related Workmentioning
confidence: 99%
“…The system presented a graph-based crime research framework that focuses on establishing relationships between the entities found in a sizable corpus of crime data from Indian states and union territories [15]. To deal with criminal situations, big data-based data analytical approaches can be applied [16]. Additionally, many data collection techniques are used for better performance, including Web 2.0, Geographic Information System (GIS), and Volunteered Geographic Information (VGI).…”
Section: Related Workmentioning
confidence: 99%